Ethics-by-Design Canvas : A Visual Inquiry Tool to Reduce Ethical Blindness in Digital Innovation Projects - Berney, Manon; Hardebolle, Cécile; Ouaazki, Abdessalam; Bartłomiejczyk, Natalia; Macko, Vladimir; Ramachandran, Vivek; Jermann, Patrick; Knight, Simon; Holzer, Adrian (My University, 2025)
Digital innovation can generate significant ethical risks, such as privacy breaches, digital addiction, or algorithmic biases. To reduce these risks, academics argue that digital innovations should focus on human well-being and flourishing rather than functionality or efficiency. However, even with these concepts in mind, the complex and often ill-structured nature of ethical risks makes it challenging for designers to identify them, a phenomenon known as ethical blindness, and develop effective mitigation strategies. To address this challenge, we introduce the Ethics-by-Design Canvas (EDC), a visual inquiry tool designed to promote ethical reflection early in the design process. By proactively identifying ethical risks, the EDC helps designers incorporate mitigation strategies from the outset, reducing the likelihood of ethical costs arising post-launch. Our evaluation results (N=26) suggest that the EDC is usable and effective in reducing ethical blindness and identifying mitigation strategies for ethical risks.